PERAN RISIKO BISNIS DALAM PENGAMBILAN KEPUTUSAN PENDANAAN PERUSAHAAN - Mahirun Mahirun (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2019)
This study aims to examine the effect of company size, sales growth, and investment opportunity set for funding policies mediated by business risk. This study also involves asset growth variables as control variables. The object of the research is all manufacturing sector companies listed on the Indonesia Stock Exchange (IDX), with observation periods ranging from 2008 to 2013 that issued R&D costs in their financial statements. The results showed that firm size had a positive and significant effect on capital structure, sales growth and asset growth had a positive but not significant effect, and the investment opportunity set had a negative and significant effect on capital structure. The effect of business risk on the capital structure is negative but not significant, while the company's size on business risk is negative but does not have a significant effect, sales growth and business risk are positive and have a significant effect, the investment opportunity set and business risks are positive and have a significant effect. The results also prove that business risk variables are not able to mediate the influence of company size, sales growth, and investment opportunity set in increasing corporate funding decisions